Analysis A Water Cooler Simulator on A Solar Cell - Teresna, I Wayan; Suparta, I Nengah (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February Edition, 2024)
Renewable energy is energy whose process is sustainable if managed properly. One of the uses of renewable energy is PLTS (Solar Power Generation). However, the temperature rise in the solar module is very influential on the voltage and electric current generated, because the solar cell will get maximum power when the temperature on the surface of the solar cell is 25 ° C. Therefore, research is carried out to optimize or increase the voltage and current generated by solar cells by analysis a Water Cooler Simulation to Solar Cells to maintain the temperature on the surface of solar cells by 31 ° C. This research was carried out measurements of temperature, voltage and current before using a water cooler simulation and after using a water cooler simulation. The results showed after using a water cooler simulation there was an increase in voltage of 1,02 V in sunny weather and 0,92 V in cloudy weather, an increase in current of 0,72 A during sunny weather and 0,70 A in cloudy weather, an increase in power of 18,37 W when the weather is sunny and 16,26 W when the weather is cloudy.